An Examination of Herd Behavior in The Indonesian Stock Market - Purba, Adi Vithara; Faradynawati, Ida Ayu Agung (The Indonesian Capital Market Review, 2012)
We examine herd behavior in Indonesian Stock Exchange, using daily and weekly stocks return from 2007 until 2010. We employ the cross sectional standard deviation of returns (CSSD methodology developed by Christie and Huang (1995) and cross sectional absolute dispersion (CSAD methodology developed by Chang et al. (2000) to detect the presence of herd behavior. Using daily and weekly CSSD, we document the nonexistence of herding behavior in Indonesian stock market. However, using CSAD of either data frequency the result demonstrates the presence of herding behavior, particularly on big capitalization and liquid stocks. The result differs from Chang et al. (2000) who find no different impact of herding behavior across size-based portfolios